2008
DOI: 10.1359/jbmr.071212
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Bone Turnover by Sex Steroids in Men

Abstract: ABSTRACT:Introduction: The mechanism(s) by which sex steroids regulate bone turnover in humans are unclear, and recent studies have suggested that follicle-stimulating hormone (FSH) may play an important role in regulating bone resorption. Materials and Methods: Fifty-nine men (median age, 69 yr) underwent suppression of sex steroids using a gonadotropin-releasing hormone (GnRH) agonist and aromatase blocker and were replaced with testosterone (T; 5 mg/d) and estradiol (E; 37.5 g/d). After assessment of bone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Consistent with these findings, clinical studies in men (median age, 69 years) who underwent suppression of sex steroids using a gonadotropin-releasing hormone (GnRH) agonist and aromatase blocker had a 60% reduction in FSH levels. Serum bone resorption markers were increased significantly in the these sex steroid-deficient men, independently of changes in FSH secretion [40]. Together, these data demonstrated that FSH does not appear to modulate in vivo bone mass in males and does not act directly on osteoclastogenesis in vitro.…”
Section: Inhibins/activinsmentioning
confidence: 70%
“…Consistent with these findings, clinical studies in men (median age, 69 years) who underwent suppression of sex steroids using a gonadotropin-releasing hormone (GnRH) agonist and aromatase blocker had a 60% reduction in FSH levels. Serum bone resorption markers were increased significantly in the these sex steroid-deficient men, independently of changes in FSH secretion [40]. Together, these data demonstrated that FSH does not appear to modulate in vivo bone mass in males and does not act directly on osteoclastogenesis in vitro.…”
Section: Inhibins/activinsmentioning
confidence: 70%
“…A combination of crosssectional and observational studies of aging men showed better correlations between serum estradiol and BMD than testosterone and BMD at various skeletal sites [Slemenda et al 1997;Khosla et al 2001Khosla et al , 2008bMellstrom et al 2008;Szulc et al 2001]. Further studies looking at differential effects between estrogen and testosterone confirmed that estrogen deficiency was more important than testosterone deficiency in causation of bone loss in aging men [Falahati-Nini et al 2000;Leder et al 2003] and that the effects of estrogen on bone were independent of FSH [Sanyal et al 2008]. More recently, a large prospective study of older men again showed a low bio-available estradiol level to be associated with significant increased fracture risk and that testosterone in the presence of high SHBG is associated with significant increased fracture risk when adjusted for estradiol levels [LeBlanc et al 2009].…”
Section: Gonadal Sex Steroid Deficiencymentioning
confidence: 99%
“…In contrast to these findings, studies by a different group with the identical FSH-receptor null mice used by Sun et al (60) did find deficits in bone mass in these mice (62). Moreover, recent findings demonstrate that at least in men, sex steroid deficiency alone is sufficient to increase bone resorption markers, even in the setting of suppressed FSH levels (63). Thus, the precise role of increases in FSH with aging in women and in men in mediating age-related bone loss remains unclear at this time.…”
Section: Role Of the Menopause In Women And Sex Steroid Deficienmentioning
confidence: 99%